Kontekstualisasi Metode Langsung dalam Pembelajaran Bahasa Arab di Yayasan Pondok Pesantren Nur An-Nahdly Tembung - Dedek Pertiwi; Sultoni Trikusuma; Susanti Nirmalasari (HIBRUL ULAMA, 2025)
This study aims to determine the effectiveness of using the Direct Method and its contextualization in the daily lives of students at the Nur An-Nahdly Tembung Islamic Boarding School Foundation. The research employed a descriptive qualitative approach, conducted during the 2021/2022 academic year with 21 students from Grade VII as the research subjects. Data collection methods included interviews, field observations, and documentation. The results indicate that Arabic language learning using the Direct Method can improve students' language proficiency, particularly in speaking skills, while also increasing student interest and motivation. This is evidenced by the improvement in students' grades and their active participation during the Arabic learning process. It can be concluded that the Arabic language proficiency of Grade VII students at Nur An-Nahdly Tembung Islamic Boarding School for the 2021/2022 academic year is considered capable and good, as many students were declared to have passed according to the established criteria.